A novel Schirmer strip-based tear matrix metalloproteinase measurement in dry eye evaluation - Chen, Di; Li, Wubi; Yang, Shan; Song, Hang; Di, Yu; Zhong, Weixing; Zhang, Miao; Long, Qin; Li, Ying; Zhao, Chan (The ocular surface, 2025)
The diagnosis and evaluation of dry eye require easy-to-use, precise, and consistent tools in clinical setting. Matrix metalloproteinase 9 (MMP-9) has been proven to be a reliable indicator of dry eye inflammation. The aim of this study is to establish an Eu-time resolved fluorescence immunochromatography (Eu-TRFICO) method for quantitative detection of MMP-9 in human tear based upon widely used Schirmer strips. The Eu-TRFICO method for Schirmer strip-based tear MMP-9 measurements were optimized and assembled. The sensitivity, repeatability and homogeneity were evaluated using MMP-9 standard dilutions. The diagnostic and treatment monitoring performance were evaluated in both dry eye patients and normal subjects. The standard curve equation was y = 0.0037 + 8.0692/[1+ (x/188.322)−0.8972] (R2 = 0.99998), and the sensitivity was 0.25 ng/mL. The Schirmer strip-based MMP-9 measurements showed acceptable repeatability and homogeneity with different saturation length in both low and high standard solutions. A total of 162 participants (162 eyes) were enrolled in this study, including 41 normal and 121 dry eye subjects. This method exhibited a sensitivity of 74.17 % and specificity of 77.5 % for dry eye diagnosis, with an AUC value of 0.8275, and cutoff value of 150.67 ng/mL, using normal subjects as negative control. The tear MMP-9 concentrations monitored with this method correlated well with the therapeutic response in dry eye patients. This study developed Eu-TRFICO Schirmer strips with high sensitivity, specificity, precision, and satisfactory clinical testing performance, which provides a convenient and quantitative option for clinical testing of tear MMP-9 in dry eye patients. •A novel Schirmer strip-based tear MMP-9 measurement with Eu-TRFICO method was developed for dry eye evaluation.•This method demonstrated a sensitivity of 74.17% and a specificity of 77.5%, with an AUC value of 0.8275 and a cutoff value of 150.67 ng/mL in dry eye diagnosis.•Tear MMP-9 levels correlated well with therapeutic responses with this method, providing a precise and convenient approach for monitoring dry eye.